2011
DOI: 10.1002/dneu.20855
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis transmembrane conductance regulator modulates synaptic chloride homeostasis in motoneurons of the rat spinal cord during neonatal development

Abstract: Cystic fibrosis transmembrane conductance regulator (CFTR) is a cAMP-regulated Cl(-) channel functional in neonatal rat spinal motoneurons. The present study investigated the developmental (P1-P8) expression of CFTR, its impact on motoneuron excitability and Cl(-) homeostasis in relation to canonical Cl(-) transporters. The Cl(-) outward transporter KCC2 gene was upregulated in females over males and increased from P1 to P8. The gene activities of the Cl(-) inward transporter NKCC1 and CFTR were positively cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…[34][35][36][37] Although expression in epithelial cells has been studied most, immune cells, 38 49 Expression of CFTR in the nervous system is particularly intriguing because chloride transport is a well-known modulator of neuronal activity. 50 In addition, as highlighted further on, many of the features of CF could manifest due to nervous system dysfunction.…”
Section: Cftr Expression and Function In The Nervous Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…[34][35][36][37] Although expression in epithelial cells has been studied most, immune cells, 38 49 Expression of CFTR in the nervous system is particularly intriguing because chloride transport is a well-known modulator of neuronal activity. 50 In addition, as highlighted further on, many of the features of CF could manifest due to nervous system dysfunction.…”
Section: Cftr Expression and Function In The Nervous Systemmentioning
confidence: 99%
“…51,52 Additional studies found CFTR expression or activity (or both) in rodent dorsal root ganglion neurons, 53 hypothalamic neurons, 54 and motor neurons. 37 In pigs, CFTR is expressed in both the peripheral and central nervous systems. 55,56 In humans, CFTR has been identified in parvocellular ganglion, 57 hypothalamic neurons, 58 spinal cord neurons, 59 ganglion cells of the heart, 60 and sympathetic ganglion.…”
Section: Cftr Expression and Function In The Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that CFTR plays a role in postsynaptic inhibition of motor neurons from the trigeminal motor nucleus during rapid-eye-movement (REM) sleep (Morales et al 2011). Recently, Ostroumov and colleagues observed that the gene activities of the chloride inward transporter, NKCC1, and CFTR were positively correlated postnatally and, using different blockers for these channels, demonstrated that inhibition of CFTR or NKCC1 activity produced a negative shift in GABA/glycine reversal potential of spontaneously occurring synaptic events measured after block of excitatory transmission, suggesting that CFTR operated together with NKCC1 to produce depolarizing GABA/glycinemediated synaptic events (Ostroumov et al 2011). The importance of chloride in the control of neuronal migration and differentiation is well known (Ben-Ari 2006) and, as with NKCC1, CFTR may also play a role in these processes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, small glial cells surrounding MNs and dorsal root ganglion neurons are strongly positive (Kanaka et al, 2001). In addition to NKCC1, the anion exchanger (AE3; Gonzalez-Islas et al, 2009, in the chick embryo) and the cystic fibrosis transmembrane conductance regulator (CFTR; Ostroumov et al, 2010) are likely to also accumulate chloride in immature MNs. In addition to NKCC1, the anion exchanger (AE3; Gonzalez-Islas et al, 2009, in the chick embryo) and the cystic fibrosis transmembrane conductance regulator (CFTR; Ostroumov et al, 2010) are likely to also accumulate chloride in immature MNs.…”
Section: Contribution Of Cation-chloride Cotransporters To the Hyperpmentioning
confidence: 99%